Facile fabrication and characterization on alginate microfibres with grooved structure via microfluidic spinning. Issue 5 (22nd May 2019) - Zhang, Xiaolin; Weng, Lin; Liu, Qingsheng; Li, Dawei; Deng, Bingyao
Abstract : Alginate microfibres were fabricated by a simple microfluidic spinning device consisting of a coaxial flow. The inner profile and spinnability of polymer were analysed by rheology study, including the analysis of viscosity, storage modulus and loss modulus. The effect of spinning parameters on the morphological structure of fibres was studied by SEM, while the crystal structure and chemical group were characterized by FTIR and XRD, respectively. Furthermore, the width and depth of grooves on the fibres was investigated by AFM image analysis and the formation mechanism of grooves was finally analysed. It was illustrated that the fibre diameter increased with an increase in the core flow rate, whereas on the contrary of sheath flow rate. Fibre diameter exhibited an increasing tendency as the concentration of alginate solution increased, and the minimum spinning concentration of alginate solution was 1% with the finest diameter being around 25 µm. Importantly, the grooved structure was obtained by adjusting the concentration of solutions and flow rates, the depth of groove increased from 278.37 ± 2.23 µm to 727.52 ± 3.52 µm as the concentration varied from 1 to 2%. Alginate fibres, with topological structure, are candidates for wound dressing or the engineering tissue scaffolds.